PERBEDAAN FONOLOGIS DAN LEKSIKAL ISOLEK SAMBORI DAN TARLAWI DI KABUPATEN BIMA - Utswatun Hasanah; Mahsun Mahsun; Burhanuddin Burhanuddin (Universitas Islam Negeri Mataram, 2025)
This study aims to describe the phonological and lexical differences between the Sambori and Tarlawi isolects. The type of research used is quantitative descriptive with a diachronic perspective. Data were collected using a research instrument that provided 200 basic Swadesh?Morish vocabulary items and 867 cultural and non-basic vocabulary items classified according to their semantic fields, employing the “cakap” method and the “simak” method. Data collection was conducted by selecting three informants from each village according to certain criteria. The data collection methods used were the “cakap” method and the “simak” method. The data analysis method employed intralingual matching with the basic technique of intralingual comparison. Further analysis calculated the percentage similarity (status) of isolects in the research area using a dialectometry method. Based on the results conducted, two phonological differences were found, namely vowel differences and consonant differences. Meanwhile, based on the calculated percentage determination of phonological differences in the research area (Sambori village and Tarlawi village) using dialectometry, a difference value of 12.5% was found, indicating a dialect difference between Tarlawi village and Sambori village at the phonological level. Then, at the lexical level, a difference value of 36.5% was found, meaning there is a sub-dialect difference between the Sambori isolect and the Tarlawi isolect.